2016
DOI: 10.4238/gmr.15017470
|View full text |Cite
|
Sign up to set email alerts
|

Coconut genome size determined by flow cytometry: Tall versus Dwarf types

Abstract: ABSTRACT. Coconuts (Cocos nucifera L.) are tropical palm trees that are classified into Tall and Dwarf types based on height, and both types are diploid (2n = 2x = 32 chromosomes). The reproduction mode is autogamous for Dwarf types and allogamous for Tall types. One hypothesis for the origin of the Dwarf coconut suggests that it is a Tall variant that resulted from either mutation or inbreeding, and differences in genome size between the two types would support this hypothesis. In this study, we estimated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The calculated ‘CATD’ genome size, however, is lower than the estimated genome size (2.42 Gbp) of the recently sequenced ‘Hainan Tall’ (HAT) coconut variety (Xiao et al 2017) by 280 Mbp. Freitas Neto et al (2016) reported that the genome size variation using flow cytometry method among 14 coconut ‘Tall’ and ‘Dwarf’ varieties is statistically small, and concluded that ‘Dwarf’ types did not really evolve from ‘Tall’ types as previously hypothesized (Perera et al 2016). We suggest otherwise, since there is a large difference between the genome sizes based on k-mer peak analysis between ‘Hainan Tall’ (Xiao et al 2017) and ‘Catigan Green Dwarf’ (this paper) whole genome sequence data.…”
Section: Resultsmentioning
confidence: 86%
“…The calculated ‘CATD’ genome size, however, is lower than the estimated genome size (2.42 Gbp) of the recently sequenced ‘Hainan Tall’ (HAT) coconut variety (Xiao et al 2017) by 280 Mbp. Freitas Neto et al (2016) reported that the genome size variation using flow cytometry method among 14 coconut ‘Tall’ and ‘Dwarf’ varieties is statistically small, and concluded that ‘Dwarf’ types did not really evolve from ‘Tall’ types as previously hypothesized (Perera et al 2016). We suggest otherwise, since there is a large difference between the genome sizes based on k-mer peak analysis between ‘Hainan Tall’ (Xiao et al 2017) and ‘Catigan Green Dwarf’ (this paper) whole genome sequence data.…”
Section: Resultsmentioning
confidence: 86%
“…This difference appears to reflect differences in assembling strategies rather than biological differences between CATD and HAIT. In fact, flow cytometry reveals intraspecific variation but to a much lesser extent and tends to yield larger values than does Kmer analysis (around C = 2.9 Gbp 28 or C = 2.7 Gbp 29 ). The CATD assembly also identified 25% more genes, resulting partially from a larger proportion of duplicated genes but also from a larger number of unique genes, especially among the smaller genes (Supplementary Fig.…”
Section: Introductionmentioning
confidence: 93%
“…are explained in detail by Greilhuber et al (2005). Furthermore, analytical tools such as flow cytometry are a reliable and convenient method to estimate genome size of plant communities such as ornamental plants (Abedi et al, 2015), medicinal plants (Javadian et al, 2017;Mahdavi and Karimzadeh, 2010;Majdi et al, 2010;Sadat Noori et al, 2017;Tarkesh Esfahani et al, 2016;Tavan et al, 2015) and fruit trees such as peach (Baird et al, 1994), olive (Brito et al, 2008;Loureiro et al, 2007b), coconut (Freitas et al, 2015), and Malus species (Hofer and Meister, 2010;Korban et al, 2009;Podwyszy nska et al, 2016). Unlike other fruit trees and plant species, there has been no study on the genome size of different walnut genotypes and cultivars, only flow cytometry is used to determine the ploidy level of walnut samples in in vitro conditions with the aim of identifying haploid plants (Sadat Hosseini Grouh et al, 2011).…”
mentioning
confidence: 99%